Crowdsourcing no Combate ao Crime em Cabo Verde - Kessy Jones Jesus Rocha (2019)
Besides the obvious benefits, the recent developments in new telecommunication technologies have brought with it a new type of organized crime. However, we should look at these new technologies not only as a threat but also as a weapon in the fight against crime. Crime, besides provoking structural tensions, promotes an absence of moral regulation within society. In Cape Verdean society, the notion of crime is provided for in the code of criminal procedure, however, in recent times a strong growth of crime rates has been happening in the country. The implementation of a crowd-sourcing system, allowing citizens of Cape Verde not only to report the occurrence of crimes, but also to assist in the recovery of stolen objects, and the possibility of access to those same data, will allow greater control and decrease petty crime in the country. This study helped to define how the rising concept of crowd-sourcing, being applied to the fight against crime in Cape Verde, can bring a series of benefits, and that the Cape Verdean society would be interested in participating in a platform of this type. The data collected through the system could also be used in research projects of the current state of the crime in Cape Verde.